2019
DOI: 10.1002/ppap.201900122
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide cross‐linking leads to pore formation: Potential mechanism behind CAP enhancement of transdermal drug delivery

Abstract: In recent years, cold atmospheric plasma (CAP) has been proposed as a novel method to enhance transdermal drug delivery, while avoiding tissue damage. However, the underlying mechanism for the increasing skin permeability upon CAP treatment is still undefined. We propose a mechanism in which CAPgenerated reactive species induce cross-linking of skin lipids, leading to the generation of nanopores, thereby facilitating the permeation of drug molecules.Molecular dynamics simulations support this proposed mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…It also facilitates the transport of nutrients into the cell from the outside and removes toxic substances from the intracellular environment [ 44 , 45 ]. Structural changes induced by RONS in the membrane can disrupt its normal permeability to certain substances [ 46 , 47 ], including RONS produced by CAP [ 48 , 49 , 50 ]. Increased entry of RONS into the cell disrupts the balance between intracellular RONS levels and the antioxidant system, resulting in oxidative stress [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also facilitates the transport of nutrients into the cell from the outside and removes toxic substances from the intracellular environment [ 44 , 45 ]. Structural changes induced by RONS in the membrane can disrupt its normal permeability to certain substances [ 46 , 47 ], including RONS produced by CAP [ 48 , 49 , 50 ]. Increased entry of RONS into the cell disrupts the balance between intracellular RONS levels and the antioxidant system, resulting in oxidative stress [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…One may suspect that besides the reactive species delivery and action on bacteria, the bacteria on the central zone of the plasma jet impact zone will rapidly be inactivated as there the electric field strength is large enough, while those on the more outer locations will require the accumulation of a larger number of electric field pulses of lower strength. Such combinatory and threshold-dependent action of pulsed electric field with reactive species was recently reported [48,[58][59][60][61] during plasma treatment of various cell lines.…”
Section: Inactivation Of Staphylococcus Aureusmentioning
confidence: 57%
“…45 CAP enhances the transcellular route by increasing the permeability of the plasma membrane through the peroxidation of lipid components in the phospholipid bilayer. [46][47][48][49][50][51] CAP also enhances intercellular delivery by suppressing the expression of cell adhesion molecules, such as E-cadherin. 37,52 Our quantification analysis confirmed that the LICAP device used in the present study could precisely adjust the reactive species production in the target solution (Figure 8A-D).…”
Section: Discussionmentioning
confidence: 99%
“…The additive effect of concurrent therapy is likely related to the ability of CAP to enhance transdermal drug delivery via transcellular and intercellular routes 45 . CAP enhances the transcellular route by increasing the permeability of the plasma membrane through the peroxidation of lipid components in the phospholipid bilayer 46–51 . CAP also enhances intercellular delivery by suppressing the expression of cell adhesion molecules, such as E‐cadherin 37,52 …”
Section: Discussionmentioning
confidence: 99%